Long-Term Unemployment and Economic Inactivity in Ukraine in the Sociological Dimension - Homanyuk, Mykola; Danylenko , Ihor; Markeliuk , Anastasia (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2021)
The article considers the causes and social consequences of long-term unemployment in Ukraine. According to the results of in-depth interviews and quantitative survey, the causes of long-term unemployment in Ukraine can be divided into three groups. The first group includes the current situation on the world labor market, the second group deals with the inside situation in Ukraine, and the third group deals with the social and psychological characteristics of the long-term unemployed. The first group of causes affects the long-term unemployment and economic inactivity indirectly. A significant number of labor migrants and high-paying freelancers among the citizens of Ukraine creates conditions for maintaining of long-term unemployment among their family members. Low wages and rapid changes in the labor market (declining demand for a number of specialties, for example engineering and technical workers), low pensions and their low differentiation, high level of the shadow and gig-economy, shortcomings in the tax sphere are the most reasons for the second group of unemployment reasons. Among the cultural reasons there are lack of knowledge of the basic principles of labor law, lack of experience in formal communication with employers, prejudice against government institutions. For a large proportion of the long-term unemployed, formal employment is associated with a decline in their social status. It was also found that the status of the official long-term unemployed largely does not correspond to their real status. The most part of them are economically quite active unofficially in shadow and gig-economy. It is concluded that the problem of including the official long-term unemployed in economic life should be reformatted into the problem of legalizing their informal economic activity.